Una falsa democrazia: governabilità vs rappresentatività - Levi, Giovanni (SocietàMutamentoPolitica, 2012)
The belief, turned in gloomy reality in the Italian society, that governability it is more important that representativeness, contributes to weaken democracy. In the long run, the same goal of governability can be jeopardized by it. A feeling of disaffection toward a politics more and more driven by professionals and leaders and less and less based upon citizen participation is arising. Nowadays this trend has grown reaching a critical point, rooted also in the historical dualism between State and society, that traditionally characterizes Italian politics.